KNOWLEDGE WORKER AS A USER OF INTELLIGENT COLLABORATIVE EDUCATIONAL SYSTEM - Katalnikova, Sabina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Education is integral part of every knowledge worker’s activity during their whole life. While talking about lifelong education of knowledge workers, it is important to provide a possibility to study following an individual programme and, keeping into mind their own particular study aim, to test their newly acquired knowledge practically, to collaborate and learn from colleagues. In this regard development and application of intelligent collaborative educational systems gain great importance. This article has a threefold purpose: 1) to analyse the notion of knowledge worker, 2) to highlight its main traits and characteristics, 3) to offer a model of knowledge worker from the standpoint of a user of intelligent collaborative educational system. This theoretical study was based on an analysis of available literature sources and a summarizing of information. In order to illustrate the proposed model, extended semantic networks were applied and their brief description was given.